2023
DOI: 10.1021/acsapm.3c00262
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of Bisphenol A-Based Thermosetting Epoxies Based on Modified Lignin

Abstract: Lignin is a highly abundant renewable natural resource with a unique structure, abundant reserves, and low cost. However, largescale utilization based on lignin still remains challenging due to its heterogeneity and inhomogeneity. Herein, we report the fabrication of tunable and mechanically tough lignin-based thermosetting epoxy resins with outstanding thermal stability by optimizing epoxidation conditions and the crosslinker. The obtained lignin-based bisphenol A composites show a tensile strength of 11.5 MP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 70 publications
0
8
0
Order By: Relevance
“…For instance, multiple literature reports demonstrated that bisphenol A (BPA) can be partially substituted by lignin to improve material properties. [76][77][78] A substitution of up to 30 wt% of bisphenol-A diglycidyl ether (BPADGE) with lignin-based epoxides is possible without negative effects on the properties of the resulting material. Instead, incorporation of lignin units into epoxy resins turned out to be beneficial for material properties, such as glass transition temperature and Young's modulus.…”
Section: Epoxide Functionalized Ligninmentioning
confidence: 99%
See 3 more Smart Citations
“…For instance, multiple literature reports demonstrated that bisphenol A (BPA) can be partially substituted by lignin to improve material properties. [76][77][78] A substitution of up to 30 wt% of bisphenol-A diglycidyl ether (BPADGE) with lignin-based epoxides is possible without negative effects on the properties of the resulting material. Instead, incorporation of lignin units into epoxy resins turned out to be beneficial for material properties, such as glass transition temperature and Young's modulus.…”
Section: Epoxide Functionalized Ligninmentioning
confidence: 99%
“…The incorporation of 10 wt% of epoxidized lignin (based on BPADGE mass) significantly improved the stiffness of the resulting material and its tensile strength (from 6.2 MPa without lignin to 10.9 MPa with lignin). 78…”
Section: Lignin Modificationmentioning
confidence: 99%
See 2 more Smart Citations
“…Lignin, the main source of natural polyphenol, has been considered as one of the most potential candidates to substitute fossil-based materials in the formulation of epoxy resins. Particularly, the low-molecular-weight oligomers derived from depolymerization or solvent fractionation of lignin demonstrated higher reactivity and better solvent solubility and could be used effectively in the preparation of lignin-based epoxy resins (LEPs) with excellent thermal and mechanical properties. Nevertheless, the practical application of LEPs as chemical cross-linkers in SP adhesive modification remains a challenge. Because the LEPs always present high viscosity and can be dispersed only with organic solvents, this makes them difficult to disperse uniformly in the water-based SP matrix, thereby reducing their reinforcement efficiencies.…”
Section: Introductionmentioning
confidence: 99%